Dynamics of Global GDP from 2015 to 2025: From Pandemic Shocks to Post-Viral Slowdown - Ubaydullayev Sirojiddin (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
Based on data from the International Monetary Fund and the World Bank, this article analyzes the dynamics of global GDP during the period 2015–2025. Three major phases are identified: pre-crisis stability (2015–2019), the shock of the COVID-19 pandemic and the subsequent V-shaped recovery (2020–2021), and the post-pandemic slowdown driven by inflationary pressures and geopolitical conflicts (2022–2025). The study substantiates the transition to a “new normal,” characterized by structurally lower economic growth rates. It also examines the differing impacts of global economic challenges on developed and developing economies and highlights the key factors shaping the trajectory of global economic development in the post-pandemic era.